Bewähren sich Bewährungsstrafen? Eine empirische Untersuchung der Praxis und des Erfolgs der Strafaussetzung von Freiheits- und Jugendstrafen - Weigelt, Enrico (Universitätsverlag Göttingen, 2009)
This research/analysis focuses on an empirical analysis of the practical criminal law and the success of suspended sentence. The foundation of the research form data sets from the Bundeszentralregister and the Erziehungsregister. About 120.000 German data sets of stayed prison sentences and stayed young offender sentences are analyzed under the following aspects: the sentence received and if the delinquent reoffends in a period of four years after their sanction. Characteristics of age, gender, nationality and perhaps an existing penal background as well as possible probation service are part of the analysis. Also discussed are connections between relapse and the revocation of the parole. Another chapter deals with the success of the suspended sentences compared to other penalties, i.e. fines and prison sentences up to two years.